Islamic Contributions to Scientific and Technological Development in Astronomy, Mathematics, Medicine, and Chemistry - Putra, Yandra Agusta; Mujab, M. (UIN Maulana Malik Ibrahim Malang, 2025)
This research discusses the contribution of Islamic civilization to the development of world science and technology and examines the role of Muslim scholars in shaping a scientific paradigm rooted in Islamic spiritual values and rationality. Based on the Eurocentric view dominating scientific historiography, the research gap identifies the urgent need for a comprehensive study that positions the Islamic contribution within an integrative, holistic, and value-based scientific paradigm. The novelty of this study lies in its comparative approach, demonstrating that Islamic scientific development possessed distinct epistemic, methodological, and ethical orientations thereby offering an alternative, ethically-oriented model of science insufficiently explored in previous research. Therefore, the purpose of this study is to reveal how Islam not only served as a medium for the transmission of knowledge from Greek civilization but also as an originator of a rational and ethical scientific method. This study uses a qualitative approach through a literature review by analyzing classical works of Muslim scholars and contemporary literature on the history of Islamic science. The results show that Muslim scholars such as Al-Battani, Al-Khawarizmi, Ibn Sina, and Al-Razi made fundamental contributions in the fields of astronomy, mathematics, medicine, and chemistry. Their contributions were not only technical but also epistemological, emphasizing the integration of revelation and reason as the foundation of knowledge pursuit. These findings indicate that the Islamic scientific paradigm is holistic, oriented toward public welfare, and rejects the dichotomy between science and religion. The implications of this research highlight the importance of reconstructing the epistemology of Islamic science in contemporary education and research contexts to build a just and sustainable civilization of knowledge. Thus, the reconstruction of Islamic science epistemology is not merely a historical endeavor, but a strategic step to rebuild the orientation of science rooted in the values of monotheism, ethics, and universal welfare. Penelitian ini membahas kontribusi peradaban Islam terhadap perkembangan ilmu pengetahuan dan teknologi dunia serta menguji peran para ilmuwan Muslim dalam membentuk paradigma ilmiah yang berakar pada nilai-nilai spiritual dan rasionalitas Islam. Berdasarkan pandangan Eurosentris yang mendominasi historiografi ilmiah, kesenjangan penelitian mengidentifikasi kebutuhan mendesak akan studi komprehensif yang memposisikan kontribusi Islam dalam paradigma ilmiah yang integratif, holistik, dan berbasis nilai. Kebaruan dari studi ini terletak pada pendekatan komparatifnya, yang menunjukkan bahwa perkembangan ilmu pengetahuan Islam memiliki orientasi epistemik, metodologis, dan etis yang berbeda, sehingga menawarkan model ilmu pengetahuan alternatif yang berorientasi etis yang belum cukup dieksplorasi dalam penelitian sebelumnya. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengungkapkan bagaimana Islam tidak hanya berfungsi sebagai media transmisi pengetahuan dari peradaban Yunani, tetapi juga sebagai pencetus metode ilmiah yang rasional dan etis. Studi ini menggunakan pendekatan kualitatif melalui tinjauan literatur dengan menganalisis karya-karya klasik para ilmuwan Muslim dan literatur kontemporer tentang sejarah ilmu pengetahuan Islam. Hasil penelitian menunjukkan bahwa ilmuwan Muslim seperti Al-Battani, Al-Khawarizmi, Ibn Sina, dan Al-Razi memberikan kontribusi mendasar dalam bidang astronomi, matematika, kedokteran, dan kimia. Kontribusi mereka tidak hanya bersifat teknis tetapi juga epistemologis, menekankan integrasi wahyu dan akal sebagai fondasi pencarian pengetahuan. Temuan-temuan ini mengindikasikan bahwa paradigma ilmiah Islam adalah holistik, berorientasi pada kesejahteraan publik, dan menolak dikotomi antara sains dan agama. Implikasi dari penelitian ini menyoroti pentingnya merekonstruksi epistemologi ilmu pengetahuan Islam dalam konteks pendidikan dan penelitian kontemporer untuk membangun peradaban pengetahuan yang adil dan berkelanjutan. Dengan demikian, rekonstruksi epistemologi ilmu pengetahuan Islam bukan sekadar upaya historis, melainkan langkah strategis untuk membangun kembali orientasi ilmu pengetahuan yang berakar pada nilai-nilai tauhid, etika, dan kesejahteraan universal.